Microfluidic mixing probe: generating multiple concentration-varying flow dipoles - Dima Samer Ali; Ayoub Glia; Pavithra Sukumar; Muhammedin Deliorman; Mohammad A. Qasaimeh (Scientific Reports)
Abstract This study advances microfluidic probe (MFP) technology through the development of a 3D-printed Microfluidic Mixing Probe (MMP), which integrates a built-in pre-mixer network of channels and features a lined array of paired injection and aspiration apertures. By combining the concepts of hydrodynamic flow confinements (HFCs) and “Christmas-tree” concentration gradient generation, the MMP can produce multiple concentration-varying flow dipoles, ranging from 0 to 100%, within an open microfluidic environment. This innovation overcomes previous limitations of MFPs, which only produced homogeneous bioreagents, by utilizing the pre-mixer to create distinct concentration of injected biochemicals. Experimental results with fluorescent dyes and the chemotherapeutic agent Cisplatin on MCF-7 cells confirmed the MMP’s ability to generate precise, discrete concentration gradients with the formed flow dipoles, consistent with numerical models. The MMP’s ability to localize drug exposure across cell cultures without cross-contamination opens new avenues for drug testing, personalized medicine, and molecular biology. It enables precise control over gradient delivery, dosage, and timing, which are key factors in enhancing drug evaluation processes.